Dietary supplementation with isochlorogenic acid improves growth performance and intestinal health of broilers - Siyuan Zhou; Haotian Jiang; Yujia Wang; An Yan; Guohua Liu; Shudong Liu; Baojiang Chen (Animal Nutrition, 2025)
This study evaluated the effects of dietary supplementation with isochlorogenic acid (ICA) on growth performance and intestinal health of broilers. A total of 400 Cobb broilers (44.20 ± 0.16 g, one day old) were randomly assigned to 5 treatments (ICA supplementation at 0, 500, 1000, 2000, and 3000 mg/kg diet) with 8 replicates of 10 birds each. The experimental trial lasted for 42 d. The feed-to-gain ratio (F/G) exhibited a quadratic decrease in response to ICA supplementation during both the 1 to 42 d (P = 0.048) and 22 to 42 d (P = 0.039) periods, with the lowest F/G observed at a dietary ICA concentration of 2000 mg/kg. The apparent digestibility of calcium (P = 0.038) and crude protein (P < 0.001) exhibited a linear upward trend, and both the villus height and the villus height-to-crypt depth ratio showed a quadratic increase (P = 0.027) with ICA supplementation. Meanwhile, the relative mRNA expression of ileum claudin-1 (P = 0.003) and occludin (P = 0.048), along with the gastrointestinal pH (P < 0.05), decreased linearly, whereas the concentration of ileum secretory immunoglobulin A (P = 0.005) increased linearly with ICA supplementation. Additionally, the concentration of total volatile fatty acids (P = 0.038) in the ileum, trypsin activity (P = 0.016), the serum concentration of immunoglobulin G (P = 0.005), and the activities of serum glutathione peroxidase (GSH-Px) (P = 0.005) and superoxide dismutase (SOD) (P = 0.040) increased quadratically with ICA supplementation. Additionally, the relative mRNA expression of SOD-1 (P = 0.040) and GSH-Px (P = 0.040) in the ileum increased linearly with ICA supplementation. The abundance of Streptococcus alactolyticus was significantly higher in broilers supplemented with ICA at 2000 mg/kg compared to the control treatment (P = 0.030), and the concentration of metabolites, such as 15-deoxy-delta-12,14- prostaglandin J2, was increased by ICA supplementation. Dietary ICA enhanced broilers growth performance via increased digestive enzyme activity, leading to improved feed digestibility. Additionally, ICA improved health status by maintaining gut pH and enhancing antioxidant and immune functions. The optimal supplemental level of ICA of improving growth performance and intestinal immune function of broilers was 2000 mg/kg.